Food systems for healthier diets in Ethiopia: Toward a research agenda - Gebru, Mestawet; Remans, Roseline; Brouwer, Inge D.; Baye, Kaleab; Melesse, Mequanint B.; Covic, Namukolo M.; Habtamu, Fekadu; Abay, Alem Hadera; Hailu, Tesfaye; Hirvonen, Kalle; Kassaye, Tarik; Kennedy, Gina; et al. (International Food Policy Research Institute, 2018)
While dietary energy supply has improved, diets in Ethiopia remain low in diversity and provide insufficient amounts of protein, vitamin A, and zinc. Poor dietary quality contributes to the multiple burden of malnutrition in the country, with 38% stunting among children under five years and 24% anemia and 8% overweight among adult women. Recent Ethiopian government policies and programs call for sustainable food systems approaches aimed at achieving better nutrition for all. Such food systems approaches imply actions that include but also go beyond agriculture to consider the many processes and actors involved in food production, processing, storage, transportation, trade, transformation, retailing, and consumption. In this paper, we identify research streams to support the operationalizing of such food systems approaches in Ethiopia. To this end, we engaged with stakeholders, reviewed the literature, and applied a food systems framework to research priorities in the Ethiopian context. We develop an initial food systems profile of Ethiopia and identify 25 priority research questions, categorized into three main areas. A first area focuses on diagnosis and foresight research, for example, to further characterize dietary gaps and transitions in the context of the variety of Ethiopian settings, and to understand and anticipate which food system dynamics contribute positively or negatively to those trends. A second area includes implementation research and focuses on building a base of evidence on the dietary impact of combined demand-, market-, and supply-side interventions/innovations that focus on nonstaples; potential trade-offs in terms of economic, social, and environmental outcomes; and interactions between food system actors. A third area focuses on institutional and policy processes and explores enabling factors and private or public anchors that can take food systems approaches for healthier diets to a regional or national scale. The paper contextualizes the case of Ethiopia within global food systems thinking and thereby aims to stimulate in- and cross-country learning.